The incidence of radiolucent lines in cemented attune total knee arthroplasty- a retrospective clinical and radiological study - Sorbi, Reza; Walker, Tilman; Nees, Timo A.; Renkawitz, Tobias; Moradi, Babak; Reiner, Tobias (Archives of orthopaedic and trauma surgery, 2025)
INTRODUCTION: The Attune total knee arthroplasty (TKA) system was introduced with the goal to improve clinical outcome, patient satisfaction and implant survival. The aim of the present study was to investigate the clinical and radiological outcome of the cemented Attune knee and to assess the rate of radiolucent lines (RLL) at a median follow-up of 4 years. - MATERIALS AND METHODS: In this single-center cohort study, we retrospectively evaluated the clinical and radiological results of 165 consecutive patients following cemented TKA with the original design of the Attune knee at a minimum follow-up of two years. Postoperative radiographs were assessed for RLL and clinical outcome was measured using patient reported outcome scores. - RESULTS: A total of 115 patients (127 knees) were available for assessment at a mean follow-up of 47.8 ± 12.9 months. The overall incidence of femoral and tibial RLL was 24% and 26%, respectively. Of the original cohort, two patients had to be revised during the course of the study, resulting in a survival rate of 98.9% at two years with the endpoint "revision for any reason". Clinical outcome scores improved significantly up to the latest follow-up. - CONCLUSIONS: The findings of this study demonstrated good clinical results with significant improvement in pain and knee function and acceptable revision rates at a median follow-up of 4 years. However, a high incidence of periprosthetic RLL was seen in this cohort. No implant showed signs of component loosening, but patients with RLL should be monitored closely and future studies with longer follow-up durations are necessary to investigate the influence of these radiolucencies on the long-term performance of this knee system.
Gesehen am 08.09.2025